2004
DOI: 10.1002/chin.200449214
|View full text |Cite
|
Sign up to set email alerts
|

A Short Enantioselective Synthesis of (R)‐(+)‐γ‐Jasmolactone.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Conversely, all optically active 1 derivatives obtained from 3a 2nd -3f 2nd showed levorotation. Clososki et al reported that (R) -1a undergoes dextrorotation 30) , whereas Missio et al reported that (S) -1a undergoes levorotation 31) . Based on these results, the absolute configurations of (+) -and (−) -1a were determined.…”
Section: Determination Of Absolute Configuration Of Opticallymentioning
confidence: 99%
“…Conversely, all optically active 1 derivatives obtained from 3a 2nd -3f 2nd showed levorotation. Clososki et al reported that (R) -1a undergoes dextrorotation 30) , whereas Missio et al reported that (S) -1a undergoes levorotation 31) . Based on these results, the absolute configurations of (+) -and (−) -1a were determined.…”
Section: Determination Of Absolute Configuration Of Opticallymentioning
confidence: 99%